Impacts of Domestic Maize Price Changes on the Performance of Small-scale Broiler Farming in Indonesia - S J K Umboh; D B Hakim; B M Sinaga; I K Kariyasa (Faculty of Animal Science, Bogor Agricultural University, 2014)
This research aimed at analyzing the impact of maize price changes on the performance of small-scale broiler farming in Indonesia using a multimarket model analysis. The multimarket model analysis is partial equilibrium analysis that contains six blocks of equations: prices, supply, input demand, consumption, income and equilibrium. This model analysis was originally designed in General Algebric Modelling System (GAMS) using the Path NLP solver. Employed data in this study were classified into 3 types, namely: (1) production and input, consumption, and household income; (2) inputs and outputs, and (3) elasticities. Decreased domestic maize price was responded by farmer through reducing maize planted area and fertilizers uses. It further had undesired impact on the maize production and maize farmer’s income. Whereas, this policy had positive impact on meat production and small-scale broiler farming income. The opposite impact will happen on those variables, if government increases domestic maize price. This policy caused the maize demand for feed industry decreased. As a result of this condition, it decreased the chicken meat production and small-scale broiler farming income.Key words: maize, broiler, price, multimarket